Miljenko Jergović w Polsce i o Polsce — na marginesie komentarza do powieści Wilimowski - Kurtok, Antonina (Przekłady Literatur Słowiańskich, 2017)
Miljenko Jergović in and about Poland — Notes in the Margin while Discussing Wilimowski the Novel The article gives a brief summary of Miljenko Jergović’s literary presence in Poland. It concentrates upon the writer’s poems, short stories, novels and essays hitherto translated into Polish and published in Poland. Additionally, Jergović’s manifold connections with Poland are presented, starting with the history of his cooperation with Magdalena Petryńska, who translated all of his novels into Polish. This translator’s impact on the writer’s popularity in our country is underscored. Within this scope, the article concentrates on the Jergović’s “most Polish” work, a short novel entitled Wilimowski. Thanks to Petryńska’s efforts, the book was published in Polish in April 2016, which constituted the novel’s world premiere. The article concisely addresses and describes the circumstances of Wilimowski’s several editions, concurrently discussing motives behind the writer’s interest in Poland (among others, the novel’s protagonist — a Polish football player Ernest Wilimowski), and the book’s reception in Poland. Last but not least, Jergović’s writing technique is characterized along with leitmotifs of his literary works. Keywords: Miljenko Jergović, Croatian literature, Polish translations, reception